2005
DOI: 10.1523/jneurosci.4880-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Polysialylated Neural Cell Adhesion Molecule Is Necessary for Selective Targeting of Regenerating Motor Neurons

Abstract: It is well established that peripheral nerves regenerate after injury. Therefore, incomplete functional recovery usually results from misguided axons rather than a lack of regeneration per se. Despite this knowledge very little is known about the molecular mechanisms regulating axon guidance during regeneration. In the developing neuromuscular system the neural cell adhesion molecule (NCAM) and its polysialic acid (PSA) moiety are essential for proper motor axon guidance. In this study we used a well establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 70 publications
9
81
1
1
Order By: Relevance
“…Although mistargeting of motor axons to the skin was not examined by Tang et al (1992Tang et al ( , 1994, a recent study by Franz et al (2005) showed that regenerating motor axons have a higher than normal propensity to grow along cutaneous nerves if they do not express PSA. Inspired by these studies, we investigated whether PSA was differentially expressed by eGFP ϩ axons innervating the longissimus muscle and skin.…”
Section: Es Cell-derived Motoneurons Innervating the Longissimus Muscmentioning
confidence: 99%
“…Although mistargeting of motor axons to the skin was not examined by Tang et al (1992Tang et al ( , 1994, a recent study by Franz et al (2005) showed that regenerating motor axons have a higher than normal propensity to grow along cutaneous nerves if they do not express PSA. Inspired by these studies, we investigated whether PSA was differentially expressed by eGFP ϩ axons innervating the longissimus muscle and skin.…”
Section: Es Cell-derived Motoneurons Innervating the Longissimus Muscmentioning
confidence: 99%
“…Therefore, recombinant EndoN enzyme, which selectively degrades polySia residues from NCAM (Rutishauser et al, 1985;Marx et al, 2001;Franz et al, 2005), was used to specifically remove PSA from the differentiating brain at 33 hpf, shortly after the onset of PSA-NCAM expression in the cerebellum (Marx et al, 2001). The efficiency of PSA removal in EndoN-and phosphate buffered saline (PBS) -treated control embryos was monitored by immunohistochemistry using the mAb735 anti-PSA antibody at 2 and 24 hr after injection.…”
Section: Psa Removal Impairs Migration Of Url-derived Cerebellar Neurmentioning
confidence: 99%
“…Another characteristic of sialylated glycan structure in the brain is polysialic acid (polySia), 3 a homopolymer of Ͼ90 sialic acid residues attached to selected proteins (13,14). PolySia modulates cell-cell interactions, thus playing important roles in neuronal development and regeneration (15)(16)(17). Recently, it was suggested that polySia also serves as a reservoir of growth factors (18,19).…”
mentioning
confidence: 99%